Factors That Influence The External Auditor's Assessment Of The Risk Of Fraud: An Auditor’s Perception - hadi mahmudah; Noviriliza Nadia Putri; Neneng Lasmita (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
ABSTRACT Financial reporting fraud has become a concern for the accounting profession in Indonesia. The accounting profession specifically issued Audit Standards Section 316 in response to the emergence of fraudulent financial reporting. One of the rules of the standard is the discussion of fraud risk assessment. This study aims to examine the effect of professional skepticism, independence, client narcissism, and time pressure on the risk assessment of fraud. This study uses primary data by distributing questionnaires to auditors who work in the DKI Jakarta area. The total respondents of this study were 120 auditors. The method of analysis used to test the hypothesis is multiple regression using SPSS version 22 software. The results of this study indicate that professional skepticism has a positive and significant effect on the risk assessment of fraud, independence has a positive and significant effect on the risk assessment of fraud, client narcissism has a positive and insignificant effect on the risk assessment of fraud, and time pressure has a negative and insignificant effect on the risk assessment of fraud. Keywords: professional skepticism, independence, client narcissism, time pressure, the auditor's fraud risk assessment.